Traditional Knowledge as a Basis for the Development of a Sustainable Resource Management Program: A Case Study in a Rural Village in Morelos, Mexico - Rubén Hernández-Tapia; Teresa Valverde; Abel Aranda; Concepción Martínez-Peralta; Diana Platas-Neri (Ethnobiology Letters, 2018)
We analyzed the traditional knowledge and management of local wild fauna and flora among the inhabitants of the peasant community of Chimalacatlán, together with their perception of local environments, to identify potential species for the future development of a sustainable resource management program. Initial contact with the community was established through an ethnographic survey to identify those with the most knowledge on this topic. Residents were selected for inclusion in the interviews using chain referral sampling. Forty-eight people were interviewed and asked about the species they were familiar with, as well as their methods of fostering/managing some of them. In this context, people cited 83 plant and 44 animal species. The preferred animals for the development of a resource management program were Odocoileus virginianus (white-tailed deer) and Ctenosaura pectinata (Mexican spiny-tailed iguana); while the preferred plants were Amphipterygium adstringens (cuachalalate) and Bursera linanoe (linaloe). For the residents of this community, fauna and flora have constituted an important resource, since various species are used as food, medicinal remedies, firewood, ornaments, and pets. Some species are illegally hunted and/or marketed as a means of subsistence. This study confirms the value of local residents’ knowledge in improving the management of environmental units, as well as the need to strengthen collaboration between decision-makers in development programs and the community.